4-1BB Costimulatory Signals Preferentially Induce CD8(+) T Cell Proliferation and Lead to the Amplification In Vivo of Cytotoxic T Cell Responses - Shuford, Walter W. (The Rockefeller University Press, 1997)
The 4-1BB receptor is an inducible type I membrane protein and member of the tumor necrosis factor receptor (TNFR) superfamily that is rapidly expressed on the surface of CD4(+) and CD8(+) T cells after antigen- or mitogen-induced activation. Cross-linking of 4-1BB and the T cell receptor (TCR) on activated T cells has been shown to deliver a costimulatory signal to T cells. Here, we expand upon previously published studies by demonstrating that CD8(+) T cells when compared with CD4(+) T cells are preferentially responsive to both early activation events and proliferative signals provided via the TCR and 4-1BB. In comparison, CD28-mediated costimulatory signals appear to function in a reciprocal manner to those induced through 4-1BB costimulation. In vivo examination of the effects of anti-4-1BB monoclonal antibodies (mAbs) on antigen-induced T cell activation have shown that the administration of epitope-specific anti-4-1BB mAbs amplified the generation of H-2(d)–specific cytotoxic T cells in a murine model of acute graft versus host disease (GVHD) and enhanced the rapidity of cardiac allograft or skin transplant rejection in mice. Cytokine analysis of in vitro activated CD4(+) and CD8(+) T cells revealed that anti-4-1BB costimulation markedly enhanced interferon-γ production by CD8(+) T cells and that anti-4-1BB mediated proliferation of CD8(+) T cells appears to be IL-2 independent. The results of these studies suggest that regulatory signals delivered by the 4-1BB receptor play an important role in the regulation of cytotoxic T cells in cellular immune responses to antigen.